5PSQ-020 Safety evaluation of injectable potassium chloride prescriptions in hospital. (March 2019) - Taouk, JB; Taouk, B; Diracca, M; Pieri, E; Gayetty, S; Raymond, F; Nassibian, C; Salini, S
Abstract : Background: Errors in the administration of injectable potassium chloride (KCl) is part of a list of 12 events described by ANSM (French drug safety agency). These events are called 'Never-Events', which should never occur in hospital if preventive measures are applied. Purpose: We wanted to know the level of safety of our injectable KCl prescriptions using ANSM safety criteria. Material and methods: We carried out a 2 week transversal-retrospective study. Between 1 July and 15 2018 each nominal prescription of injectable KCl was included using our pharmacy validation software (DXCare). All services were included except the ICU and emergencies. Then an intern in the pharmacy processed analyses of the following safety criteria. A double-check was made by a senior pharmacist. The reference guideline used for the safety criteria was the 2017 ANSM recommendations for injectable potassium chloride. For each prescription, recommended ANSM safety criteria related to intravenous KCl were assessed: Indication of severe hypokalaemia (<3 mmol/L) or inability to swallow. Prescription of KCl using specific units (g or mmol). Use of a slow infusion rate (≤1 g/h). Use of the available ready–to–use solution. Mention of the nature of the dilution solution to be used. Final concentration of the KCl infusion ≤4 g/L. Mention of the final volume of the KCl infusion. Results: One-hundred and four patients were included. 30.7% (95% CI: ±8.9%) of the prescriptions were relevant in term of indication. 38 4% (95% CI: ±9.35%) of the prescriptions used the correct specific units. In 99, 1% (95% CI: ±1.82%) of cases the correct slow infusion rate was prescribed. In 15.3% (95% CI: ±6.9%) of cases a ready–to–use solution was prescribed. Mention of the nature of the dilution solution to be use was found in 84.6% (95% CI: ±6.9%) of cases. Final concentration of the KCl infusion was ≤4 g/L in 73% (95% CI: ±8.5%) of cases. Mention of the final volume of the KCl infusion was detailed in 82.6% (95% CI: ±7.29%) of cases. Conclusion: Indications to use injectable KCl were not strictly applied, which may be explained by prescribing habits and the desire to quickly normalise hypokalaemia. A very low utilisation of ready-to-use products which is probably due to insufficient information to prescribers concerningt the available ready-to-use products. Most prescriptions were not using the recommended units, and lack of knowledge of the prescriber of the need to prescribe in g or mmol may be the cause of this. References and/or acknowledgements: No conflict of interest.